Effect of Irrigating Cooler Water (ICWr) on The Canopy Temperature of Japonica Rice Cultivars Himenorin and Nikomaru - Nazif Ichwan; Taufiq Yuliawan; Augustine Ukpoju; Hiroki Oue (Journal of Natural Resources and Environmental Management)
The canopy temperature of rice is a critical concern due to rising air temperatures and the increasing risk of heat damage. In this study, we investigated the canopy temperature difference (CTd) and canopy temperature depression (CTD) in the Japonica rice cultivars ‘Himenorin’ (HR) and ‘Nikomaru’ (NM). Additionally, we examined the effect of irrigating cooler water (ICWr) on canopy temperature, particularly its impact on CTD reduction, compared to a control plot. The results showed that CTd in HR was lower than in NM. Furthermore, CTD reached 2.23 °C in HR and 2.35 °C in NM under shallower ponding conditions. ICWr effectively reduced the canopy temperature in both cultivars and decreased CTD to a negative value. These findings highlight that ICWr can mitigate canopy temperature increases under more intense solar radiation and high air temperatures. Therefore, implementing ICWr in rice fields may serve as a potential countermeasure to reduce heat damage in rice by lowering canopy temperature. Further research is necessary to elucidate the underlying mechanisms and enhance strategies for mitigating heat exposure, ensuring rice resilience and sustainability in a changing climate.